Kecerdasan Logika Matematika, Efikasi Diri dan Motivasi Berprestasi Terhadap Perilaku Inovatif - Permana, Adi; Rusmana, Indra Martha (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The purpose of this study is to get answers empirically: (1) The Effect of Mathematical Logic on Innovative Behavior, (2) The Effect of Self-Efficacy on Innovative Behavior. (3) The Effect of Achievement Motivation on Innovative Behavior. (4) The Joint Effect of Mathematical Logic Intelligence, Self-Efficacy and Achievement Motivation on Innovative Behavior. The method used in this research is a survey method with multiple linear regression approach. The research sample was 40 SMK students in Sawangan sub-district which was determined by random sampling technique. Based on the results of this study, it can be concluded that: (1) There is a partial positive and significant influence of the Mathematical Logic variable on the Innovative Behavior variable, (2) There is a partial positive and significant influence on the Self-Efficacy variable on the Innovative Behavior variable. (3) There is a positive and significant influence of the achievement motivation variable partially on the variable of innovative behavior. (4) There is a positive and significant influence on the variables of Mathematical Logical Intelligence, Self-Efficacy and Achievement Motivation simultaneously on Innovative Behavior. The higher the mathematical logic, the better the self-efficacy and the higher the achievement motivation, the higher the student's innovative behavior.